"I just don't feel comfortable speaking English": Foreign language anxiety as a catalyst for spoken-language barriers in MNCs. Issue 4 (August 2017) - Aichhorn, Nathalie; Puck, Jonas
Highlights: Language has moved in the focus of international business research. Existing research provides strong evidence of the existence of language barriers. We conceptualize Foreign Language Anxiety (FLA) as an underlying emotional mechanism adding to the creation of a language barrier. We show that emotions are, besides cognitive factors, an important factor in creating a language barrier. FLA can be found across all cultural and institutional background in the study. Abstract: Over the last two decades, the impact of language standardization in MNCs has attracted considerable research attention. However, although the current IB literature strongly suggests that the introduction of English can cause a significant barrier, we still have not fully understood the micro-foundations of such barriers. We conducted an inductive study and interpret our findings using an interdisciplinary approach drawing from both IB related research as well as research from the field of linguistics and language studies. We propose that a major challenge for MNC employees is the foreign language anxiety they typically experience in a non-native language. It is manifest in communication avoidance and withdrawal, as well as code-switching. Our findings indicate that such communicative behaviors can have a considerable impact on interpersonal communication, affecting both the content and relationship dimension. Our study contributes to emerging research on the role of anxiety-related factors as micro-foundations of language barriers and provides a so far rather neglected starting point for firms to reduce the language barrier in corporations.